Construção de proposta metodológica para mapeamento participativo de mobilidade urbana : estudo no "Território do Bem"-bairro São Benedito-Vitória/ES - Pinho, Talita Guimarães Fonseca de (2015)
The participatory mapping is built as a tool in order to favor specific communities’ social rights consolidation. It contributes to concretization of principles and democratic practices. In order to make participation the base of the process, it is necessary to adopt specific methodologies though. They would guide the planned activities complying with the interested community’s characteristics and necessities. The methodologies of participatory mapping have been developed more often by traditional communities and also in the countryside, rarely in informal occupations of urban situations. This research aims the organization of a methodological procedure for participatory mapping, focusing on urban mobility in high occupational density areas and low infrastructure. It uses as reference, the São Benedito district, located in Vitória/ES, specifically on a region named “Território do Bem”. Therefore this study presents bibliographic revision about participatory mapping and the existing geographical elements and its influence in this district. They are pertinent for the development of the participatory mapping, considering the aspects of the region “Território do Bem”. It discourses about the context of the communities mentioned and systematizes the participatory mapping experiences. It also proposes the participatory mapping methodology for urban mobility. Interviews and observations in the studied area were taken. They were supported by the Non Governamental Organization “Ateliê de Ideias”, partering with LabTTEC-Ifes, in the “Mapa do Bem” project. The built methodological proposition was discussed with social actors who were relevant to the theme, viewing its validation. It has been discussed in the final considerations that it is necessary to evolve a lot in order to make the mapping really participatory. It was noticed that the geo-referenced technologies innovations collaborate a whole lot for that. It is discussed about the mobility suggestions in the “Território do Bem” region. It has a rich population in contrast and also has active participation.